2015
DOI: 10.1007/s11082-015-0145-y
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Ce doping on the structural and optoelectronic properties of RF-sputtered ZnO films

Abstract: Using X-ray diffraction, UV-Visible spectroscopy, XPS and photoluminescence (PL) measurements, the structural, optical and electronic properties of ZnO and Cedoped ZnO thin films were investigated; the films were deposited on glass substrates by RF reactive-magnetron sputtering and post-annealed at 300 C in an oxygen atmosphere. Under similar deposition conditions, both films crystallized into hexagonal würzite lattice structures. The pure ZnO film exhibited a c-axis preferential orientation, whereas the Cedop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…Here, the improvement in crystal quality of the films should mainly be due to the high temperature annealing, but since the ratio is larger for the Ce and/or Yb doped films, it can be hypothesized that the RE ions can contribute to the improvement. It has been reported that Ce doping can contribute to a quality improvement [23,24,25]. Here the Ce doped film (S5) has the highest I NBE /I VIS ratio, and the Ce + Yb doped sample films (S1-4) have comparable I NBE /I VIS ratios, as predicted by the hypothesis.…”
Section: Methodssupporting
confidence: 70%
See 1 more Smart Citation
“…Here, the improvement in crystal quality of the films should mainly be due to the high temperature annealing, but since the ratio is larger for the Ce and/or Yb doped films, it can be hypothesized that the RE ions can contribute to the improvement. It has been reported that Ce doping can contribute to a quality improvement [23,24,25]. Here the Ce doped film (S5) has the highest I NBE /I VIS ratio, and the Ce + Yb doped sample films (S1-4) have comparable I NBE /I VIS ratios, as predicted by the hypothesis.…”
Section: Methodssupporting
confidence: 70%
“…Notably S5 has the highest ratios among the films at all the temperatures. Generally, the increase of the I NBE /I VIS ratio is often regarded to be due to the film crystal quality being improved [23], while some caution should be exercised in using that approximate general tendency to compare situations. Here, the improvement in crystal quality of the films should mainly be due to the high temperature annealing, but since the ratio is larger for the Ce and/or Yb doped films, it can be hypothesized that the RE ions can contribute to the improvement.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the presence of ceria limits the growth of the ZnO phase, decreasing the crystallite size. The interaction between the two different phases (ZnO and CeO 2 ) and the formation of heterojunctions at boundaries limits the growth of the particles themselves . These assumptions were confirmed by TEM analysis in Figure where it is evident the difference in size between CeO 2 and ZnO particles.…”
Section: Resultssupporting
confidence: 53%
“…The nonstoichiometry of films springs from loosely bound oxygen on the surface, other than lattice oxygen. Further details about conducted XPS analysis can be found elsewhere [19].…”
Section: Methodsmentioning
confidence: 99%